CUTIS-SEQ, a flexible bilocus sequence typing scheme that provides high resolution of Cutibacterium acnes strains across all subspecies. (February 2023) - McLaughlin, Joseph; Nagy, István; Miliotis, Georgios; McDowell, Andrew
Abstract: Objectives: A 'high resolution' Single Locus Sequence Typing (SLST) scheme has been described for the anaerobic skin bacterium Cutibacterium acnes that seemingly discriminates sequence types (STs) to a level commensurate with previously described Multilocus Sequence Typing (MLST) methods (MLST4 ; MLST8 ; MLST9 ). However, no quantifiable evaluation of SLST versus MLST for differentiation of C. acnes strains, especially in relation to the subspecies of the bacterium, known as C. acnes subsp. acnes (type I), C. acnes subsp. defendens (type II) and C. acnes subsp. elongatum (type III), has been performed which is vital given its increasing use. To address this, we examined the discriminatory power of SLST versus MLST with a large group of isolates representative of all subspecies. Methods: Simpson's index of diversity ( D ) was used for quantitative comparison of the resolving power of the SLST and MLST schemes for 186 isolates of C. acnes covering all three subspecies. Results: When strains were considered collectively, SLST and all three MLST approaches had similar D values > 90%. However, at the subspecies level there were significant differences between the methods, most strikingly a reduced discrimination of type II and type III strains ( D <80%) by SLST versus MLST8, and to a lesser extent MLST4 . The MLST9 method also performed poorly for type II strains ( D <70%), but did display the best results for type I ( D  = 90%). By combining the SLST locus with the camp2 gene sequence to create a novel and flexible high-resolution Bilocus Sequence Typing (BLST) scheme, known as CUTIS-SEQ typing (CUTI bacterium acneS BilocuS sEQ uence Typing), we achieved improved resolution at both species and, critically, subspp. levels. Conclusions: CUTIS-SEQ provides an opportunity to improve differentiation of C. acnes isolates by SLST without significantly impacting laboratory workload, or compromising application to complex biological communities. A CUTIS-SEQ isolate database is now available as part of the C. acnes PubMLST database at https://pubmlst.org . Highlights: SLST and MLST have similar discriminatory power at the species level. However, SLST has a greatly reduced ability to resolve type II and III strains. Combining the SLST and camp2 loci provides higher resolution across all phylotypes. This scheme, known as CUTIS-SEQ, has an isolate database at https://pubmlst.org .